Housing occupancy and costs, Australia - Australian Bureau of Statistics (Canberra, A.C.T. : Australian Bureau of Statistics, 1997)
Contains data from the continuous Survey of Income and Housing Costs on housing costs such as rates, mortgage and rent payments and relates these to characteristics of occupants such as age, income and principal source of income. The publication uses the "current income" concept (i.e. weekly income), and "households" as the unit of analysis.
Catalogue no. 4130.0.
No longer published in print. Later issues available on the Internet. Address as at 22/3/06: http://www.abs.gov.au/ausstats/abs@.nsf/cat/4130.0
Keywords: Housing -- Australia -- Costs -- Statistics -- Periodicals; Home ownership -- Australia -- Costs -- Statistics -- Periodicals; Rent -- Australia -- Statistics -- Periodicals; Australian